Pharmacology, Anti-fertility Activities of Kigelia pinnata and Martynia annua Medicinal Plants - Ram Bhajan Kumawat, Dr. Priti Kaushik, Dr. Geeta Meena (International Journal of Advanced Science and Technology, 2020)
The aim of study to find out an important source of food and medicine for mankind Humanhas been used a group of plants and their natural products for different purpose from ancienttimes,they are easy to use oraly, as ailments or in natural forms with no side effects. The use of plant products is a part of traditional medicinal system (Ayurveda). Kigelia pinnata and Martynia annua plants have been used for several pharmacological activities in different parts around the world.